Understanding Patient Loyalty Strategy in Military Healthcare: The Influence of Service Quality, Engagement, and Unique Experiences - Dewi, Rima Kusumah; Seswanto, Pudji (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study, entitled Understanding Patient Loyalty Strategy in Military Healthcare: The Influence of Service Quality, Engagement, and Unique Experiences, aims to investigate the effects of Service Quality, Patient Engagement, and Unique Experience on Patient Loyalty, with Patient Satisfaction serving as a mediating variable. A quantitative research approach was employed, using a survey of 255 users of military healthcare services. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS software. The results indicate that Unique Experience has a positive and significant effect on Patient Satisfaction (β = 0.634; p < 0.001), whereas Service Quality (β = 0.025; p = 0.885) and Patient Engagement (β = 0.090; p = 0.637) do not exhibit significant effects. Furthermore, Patient Satisfaction has a positive and significant effect on Patient Loyalty (β = 0.856; p < 0.001). The mediation analysis reveals that Patient Satisfaction mediates only the relationship between Unique Experience and Patient Loyalty, whereas the mediating effects of Patient Satisfaction on the relationships between Service Quality and Patient Loyalty, and between Patient Engagement and Loyalty, are not supported. These findings suggest that patient loyalty in military healthcare is shaped more by unique service experiences than by service quality or patient engagement.